Determination of Return on Assets of the Foreign Exchange Banks in Indonesia - Ghazali Syamni; Rasyimah Rasyimah; Desy Ratnasari; M. Shabri Abd. Majid (Bina Nusantara University, 2018)
The purpose of this research was to examine the determinants of Return on Assets (ROA) on the foreign exchange banks in Indonesia. The data used were the financial ratios of 27 foreign exchange banks in Indonesia in 2012-2016. The data were gathered from the published financial statements of the Indonesian foreign exchange banks. This research employed a Common Effect Model (CEM) as the most suitable panel regression model to analyze the data using the E-views statistical software. The findings indicate that from 2012 to 2016, the profitability of the exchange banks is largely determined by the Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Operating Efficiency Ratio (OER), and total debt. The findings also imply that apart from maximizing profit, it is important for the banks to abide by the regulations issued by the central bank or the Financial Services Authority in performing the banking operations. Negligence to observe the level of prudential and risk management will not only lead to profit loss, but it will also cause the failure of the banks.